Analisis Tuturan Tradisi Lisan Bumbang Aji Dalam Perkawinan Masyarakat Di Sukadana, Lampung Timur: Kajian Antropolinguistik - Ghaziyah Hanifah; Irwan Suswandi; Intan Rawit Sapanti (Universitas Muhammadiyah Surabaya, 2026)
This study examines the utterances of the Bumbang Aji oral tradition in the wedding ceremony of the Lampung Pepadun community in Sukadana, East Lampung. The research aims to describe the linguistic forms and cultural values represented in sixteen verses of traditional utterances. A descriptive qualitative method was employed using simak and catat techniques based on a YouTube waroeng_umkm video documentation, supported by interviews technique with informants for data analysis clarification. The analysis applies the perspective of Edward Sapir (1921) on the relationship between language and culture. The findings reveal that the utterances are structured in parallel and repetitive verses and employ nature-based and customary object metaphors such as brass, flowers, leaves, and peacocks. These metaphors represent values of politeness, respect, deliberation, and religiosity. The language in this tradition functions as a medium of customary legitimation and reflects the collective value system of the Lampung Pepadun society.